Persepsi mahasiswa UIN Malang terhadap film animasi jumbo sebagai media edukasi identitas nasional anak di UIN Malang - Zaky, Nawwasca Auliano (Maliki Interdisciplinary Journal, 2025)
Animated films are very useful as a visual communication medium because they can convey moral messages and national values to children in an engaging and easily understandable way. This study investigates the representation of national identity in the animated film Jumbo created by Visinema Studios, which employs the semiotic approaches of Ferdinand de Saussure and Charles Sanders Peirce. Through the analysis of visual, verbal, and symbolic signs, the main character Don represents national values such as nationalism, self-resilience, solidarity, empathy, and creativity. Furthermore, visual symbols like colors, clothing, and aspects of local culture help convey national messages. The study shows that Jumbo not only serves as entertainment but also functions as a character education tool that aids children in understanding their national identity. Therefore, animated films can be a strategic tool for building national identity from an early age.